CHANGING BELIEF OF PRE-SERVICE ENGLISH TEACHERS DURING TEACHING PRACTICUM - Yayu Heryatun; Emeliya Sukma Dara Damanik (English Education Department, 2021)
This study investigated the changing belief of pre-service English teachers during they did teaching practicum. It was one of subjects in teacher education programs. Belief of pre-service English teachers played significant role as it could influence their classroom practices and teaching outcomes. The methodology of research used in this study was qualitative case study. It involved twenty pre-service English teachers from English Department. They were put in twelve schools which located in four towns in Banten Province. This study employed questionnaire and reflective journal as instruments for collecting data. The questionnaire itself was distributed before and after teaching practicum, while reflective journal was filled by twenty pre-service English teachers during teaching practicum.The results of this study revealed that the changing of teachers’ belief varied among participants. The changing belief of pre-service English teachers covered three themes, which consists of (1) learners (2) learning and (3) teaching, before and after they did teaching practicum. Dealing with the first theme, changing belief on learners, pre-service English teachers experienced more on their emotion specifically on their confident as well as patient. In addition, the second theme, changing belief on learning, it occurred more on pre-service English teachers’ awareness that the classroom reality helped them to test their knowledge and it made them more aware of their personal beliefs about learning. Moreover, the last theme, changing belief on teaching, it took place when pre-service teachers had been exposed to teaching English in real contexts EFL classroom.